Design and Realization of a Non-Destructive Testing Device Operating on Eddy Current Principle - Cung, Thanh Long; Bui, Dang Thanh; Dao, Duc Thinh; Nguyen, Van Tung (Old Journal, 2017)
This paper presents a design of a non-destructive testing device using eddy current technique. This device has a sinusoidal excitation source consisting of 4 frequencies which developed to operate with double-function eddy current sensors. The testing results are displayed on a black and white graphic LCD as a function of sensor’s output voltage to testing position, and user’s evaluation is based on the shape of this signal. Experiments on several kind of tested specimen show that this device operates stably and can detect small surface or under-surface cracks.